Assessing the maturity level of an organization in its adoption of collaboration technologies - Muñoz Rincon, Maria del Pilar (2015)
Nowadays there are many information technologies that can make a significant difference to support collaborative efforts in the workspace. The role of IT is to support group collaboration by empowering team members with the right capabilities. One way to assess capabilities is through a maturity model. This paper proposes a first version of the Collaboration-Technology Maturity model (CTMM), aiming to serve as a strategic instrument for IT managers to control and manage the adoption of Collaboration Technologies (CITs) among their organizations. Our contribution is both theoretical and practical as we propose a descriptive maturity model. Nevertheless, it is also an application method and assessment instruments. We also completed an empirical evaluation by conducting 89 assessments at Latin American companies of all sizes and industries. This extensive field exercise allowed us to not only evaluate the usefulness of the model and instruments but also investigate CIT adoption patterns in Latin America in an attempt to collect historical data to further evolve CTMM into a comparative model. Responses were used to provide conclusions on CIT adoption in Latin America with respect to three specific backgrounds: the country of origin (region), size (in number of employees) and industry type. The implications of our findings are discussed for practitioners and researchers.